A decision model to improve the performance of inventory management for deteriorating items considering temperature. (20th September 2022) - Tayal, Shilpy; Dhiman, Neeraj; Singh, S.R.
Here an inventory system for time and temperature dependent deterioration with constant demand rate has been developed. If we discuss about a cold storage warehouse then the items stored maintain its quality in a particular range of temperature. A temperature value higher or lower than this range results in an increased rate of deterioration. Considering all the possible cases of temperature the optimal value of unit time profit have been calculated at different points in the assumed range. With the help of numerical example it is concluded that unit time profit is maximum at that temperature value which is feasible for that particular item. With numerical analysis the optimality of the system in all the three cases has also shown graphically. Further to verify the system stability sensitivity analysis has been performed and the system is found to be quite stable.